Isolation of cadmium from aqueous solutions of natural sorbents with immobilized bacteria of the genus Pseudomonas - Гудзенко, Т. В.; Пузирьова, І. В.; Бєляєва, Т. О.; Волювач, О. В.; Горшкова, О. Г.; Іваниця, В. О. (Problems of Environmental Biotechnology, 2013)
Experimentally proved, that immobilized bacteria of the genus Pseudomonas increase by 20 - 30 % of the adsorption capacity of the mixture of natural sorbents (chitosan and clay 1:1 by weight). Optimal consumption of sorbents for processing 1 dm3 of water containing cadmium concentration of 100 mg/dm3, is 4 g. It is set that high affine property is shown the bacterium of the genus Pseudomonas to the high-toxic cadmium during three-seven twenty-four (depending on the races of motion of sorbent) hours. It was found that bacteria of the genus Pseudomonas are high affinity to high-toxic cadmium. Shows the ability to efficiently re-use of a mixture of chitosan and clay with immobilized bacteria to highlight cadmium from aqueous solutions with a concentration of 100 mg/dm3 on metal.